2018
DOI: 10.1080/19476337.2017.1383514
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and bioactive compounds in dried tomato processing waste

Abstract: This research investigated the nutritional and antioxidant composition of tomato processing waste with the aim to enable the development of new alternatives for the recycling of this by-product. The samples of dried tomato waste were found to contain 176.2 g/kg protein, 21.9 g/kg fat, 524.4 g/kg crude fiber and 42.1 g/kg ash. The essential amino acids represented 34.2% of total protein, the most abundant being leucine, followed by lysine and isoleucine. Unsaturated fatty acids represent 77.04% of the total fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
73
8
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 39 publications
12
73
8
4
Order By: Relevance
“…Carotenoids content (all-trans lutein, β-carotene and all-trans lycopene) of tomato waste powder obtained from organic tomatoes was higher than carotenoids content of that obtained from conventional ones (table 6). Also, βcarotene and all-trans lycopene content of tomato waste powders, within this study was higher than carotenoids content reported by Nour et al [23] (9.56 mg/100g β-carotene and 51.06 mg/100g lycopene).…”
Section: Methods Applicationcontrasting
confidence: 67%
See 1 more Smart Citation
“…Carotenoids content (all-trans lutein, β-carotene and all-trans lycopene) of tomato waste powder obtained from organic tomatoes was higher than carotenoids content of that obtained from conventional ones (table 6). Also, βcarotene and all-trans lycopene content of tomato waste powders, within this study was higher than carotenoids content reported by Nour et al [23] (9.56 mg/100g β-carotene and 51.06 mg/100g lycopene).…”
Section: Methods Applicationcontrasting
confidence: 67%
“…Studies performed by Rubashvili et al (2018) showed that in case of tomato skin β-carotene content varied in the range 8.39 -12.75 μg/g, and lycopene content in the range 165.11 -179.56 μg/g [22]. According to the recent studies performed by Nour et al (2018) dried tomato wastes, consisting of about 22.2% seeds and 77.8% pulp residues and skins, have complex biochemical composition represented by: 946.5 g/kg dry matter, 176.2 g/kg crude protein, 21.9 g/kg crude fat, 524.4 g/kg crude fiber, 42.1 g/kg ash, 172.4 g/kg total amino acids, unsaturated fatty acids (represent 77.04% of the total fatty acids), saturated fatty acids (represent 22.72% of the total fatty acids), 1229.5 mg GAE/kg total phenolics, 415.3 mg QE/kg total flavonoids, 510.6 mg/kg lycopene, 95.6 mg/kg β-carotene [23]. Strati et al (2012) developed a method for carotenoids determination in tomato wastes by high-performance liquid chromatography (HPLC-DAD), using a YMC (Tokyo, Japan) C30 column (250 × 4.6 mm I.D., 5 μm particle).…”
Section: *Email: Email: Mcatana1965@gmailcommentioning
confidence: 99%
“…No significant differences were recorded for pressure on chlorogenic acid content (Table 3). High content of chlorogenic acid has been also found in tomato processing waste by Nour et al (2018).The effect of applying pressure on phenolic extraction was monitored using quercetin, epicatechin, catechin, naringenin and luteolin s markers. Data analysis highlighted how the increase in pressure led to a rise in the extraction performance of both epicatechin (respectively 1.08 mg/kg DW vs 2.83 mg/kg DW at 350 and 550 bar) and catechin (respectively 3.12 mg/kg DW vs 4.22 mg/kg DW at 350 and 550 bar).…”
Section: The Effect Of Extraction Parameters On Phenolicsmentioning
confidence: 99%
“…However, modern eco-compatible technologies offer more efficient strategies to recycle these by-products and reuse them as a sustainable source of different nutrients and highly biologically active compounds, such as amino acids, fatty acids, minerals and carotenoids. [1][2][3] Apart from carotenoids, i.e. lycopene and β-carotene found in major amounts, tomato by-products are also rich in phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%